Some Dramatic Scenes and Their Significance in Mulk Raj Anand’s Novel Untouchable - Adhikari, Bina (Pursuits: A Journal of English Studies, 2024)
This paper discusses about the dramatic scenes and their significance found in Mulk Raj Anand’s first novel Untouchable. From the deep study in the novel, the early morning scene, the well-scene, the touching scene, the most pathetic scene, the pollution scene, the Chapati-throwing scene and the hockey match scene are found to be focused. Bakha is a key person of the novel who is enthusiastic to hire his senses to adore the satisfaction of environment. His vocation-the duty of searching has destroyed his preferred senses. He discovers happy in nature which influences him, but he notices the impact only in a confined superficial way. It is the tiring schedule and the dirty job of cleaning toilets that have made Bakha unfit of admiring natural prettiness. Thus, the match provides the novelist with yet another occasion to depict the inhumanity of the caste Hindus and the degrading and demoralising effect of untouchability.